Homoisoflavanone prevents mast cell activation and allergic responses by inhibition of Syk signaling pathway. Issue 4 (22nd January 2014) - Lee, Y. S.; Hur, S.; Kim, T.‐Y.
Abstract Background Mast cells play important roles in allergic inflammatory responses because they produce leukotrienes (LTs), prostaglandins (PGs), and a variety of inflammatory cytokines. Thus, pharmacological interventions for allergies have focused on inhibiting mast cell activation. Homoisoflavanone (HIF), isolated from Cremastra appendiculata Makino, has anti‐angiogenic activities; however, its effects on allergic reactions have not been determined. The aim of this study was to assess the inhibitory effects of HIF on mast cell activation, which is critical for anti‐allergic reaction and the underlying mechanisms. Methods Enzyme‐linked immunosorbent assays, quantitative real‐time PCR, western blot analyses, and degranulation assay were performed to measure pro‐inflammatory and allergic mediators in PMA/A23187‐ or IgE/antigen‐stimulated mouse bone marrow‐derived mast cells (BMMCs), HMC‐1, RBL‐1, or human PBMC‐derived mast cells treated with or without HIF. The anti‐allergic effects of HIF were determined in mouse models using dinitrophenol‐immunoglobulin E‐induced passive cutaneous anaphylaxis (PCA) and compound 48/80‐induced ear swelling. Results Homoisoflavanone down‐regulated PGD2, LTB4, and LTC4 production and inhibited the production of pro‐inflammatory cytokines, such as interleukin‐6 and tumor necrosis factor‐α in PMA/A23187‐ or IgE/antigen‐stimulated mast cells. The molecular mechanisms by which HIF caused these inhibitory effects were determined to be the inactivation of spleen tyrosine kinase (Syk) signaling and the concurrent suppression of cPLA2. HIF inhibited IgE‐mediated PCA and compound 48/80‐induced ear swelling in mouse. Conclusions Homoisoflavanone inhibited mast cell activation through the suppression of Syk pathway together with the inhibition of cPLA2. Thus, it might be a good candidate molecule for allergic diseases.